2004
DOI: 10.1091/mbc.e03-07-0524
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Attachment, Meiotic Chromosome Condensation, Pairing, and Bouquet Stage Duration Are Modified in Spermatocytes Lacking Axial Elements

Abstract: During the extended prophase to the meiosis I division, chromosomes assemble axial elements (AE) along replicated sister chromatids whose ends attach to the inner nuclear membrane (NM) via a specialized conical thickening. Here, we show at the EM level that in Sycp3 ؊/؊ spermatocyte chromosomes lack the AE and the conical end thickening, but still they attach their telomeres to the inner NM with an electron-dense plate that contains T 2 AG 3 repeats. Immunofluorescence detected telomere proteins, SCP2, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
128
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(142 citation statements)
references
References 80 publications
(153 reference statements)
12
128
0
Order By: Relevance
“…Though a chromosomal cohesin core is established in the absence of an intact AE in Sycp3 -/-spermatocytes, the respective proteins, e.g. SMC1, SMC3, STAG3, localize more discontinuously and the chromosomal axes appear significantly longer than in wild-type (Yuan et al 2000;Pelttari et al 2001;Liebe et al 2004). Conversely, depletion of meiotic cohesion subunits, e.g.…”
Section: First Step: the Assembly Of The Chromosomal Axes And The Aximentioning
confidence: 96%
See 3 more Smart Citations
“…Though a chromosomal cohesin core is established in the absence of an intact AE in Sycp3 -/-spermatocytes, the respective proteins, e.g. SMC1, SMC3, STAG3, localize more discontinuously and the chromosomal axes appear significantly longer than in wild-type (Yuan et al 2000;Pelttari et al 2001;Liebe et al 2004). Conversely, depletion of meiotic cohesion subunits, e.g.…”
Section: First Step: the Assembly Of The Chromosomal Axes And The Aximentioning
confidence: 96%
“…Sycp3 -/-spermatocytes, which do not form AEs, SYCP1 can still bind to the chromosomal axes and form stretches of the CR although these are much shorter than in wild-type (Liebe et al 2004). It is possible that, in this case, the cohesin core is sufficient to allow the binding of the TFs (Pelttari et al 2001).…”
Section: Second Step: the Assembly Of The Central Regionmentioning
confidence: 99%
See 2 more Smart Citations
“…3A, B). The intensity of signals was diminished as meiosis proceeded and the signals were completely lost in secondary spermatocytes ( The oriented expression of SC components presumably reflects the polarized nuclear organization known as the meiotic bouquet structure [43,44]. Close observations using double-labeling of frozen sections with anti-MeSYCP1 and anti-MeSYCP3 antibodies revealed that some cysts of spermatocytes expressed MeSYCP3 but not MeSYCP1 (indicated by a blue arrow in Fig.…”
Section: Expression Of Mesycp1 and Mesycp3 In The Testismentioning
confidence: 98%